Evidence of fin whale (Balaenoptera physalus velifera) recovery in the Canadian Pacific - Lynn Rannankari; Rianna Burnham; David Duffus (Frontiers in Conservation Science)
Pacific fin whales (Balaenoptera physalus velifera), once the most abundant cetacean species in British Columbia (BC), were also one of the most heavily targeted by commercial whaling. Much of what we know about their phenology and ecology is from catch records, but their current status has not yet been summarized in Canadian waters. Here, we collated evidence from dedicated surveys, opportunistic sightings, and passive acoustic records that had not been reported before and reviewed them in the context of past data. This was to add new findings to what is known, and to establish if the population was showing signs of recovery. This is particularly relevant considering discussions of downlisting their population status in Canada from endangered to threatened. We then asked if this rebounding was consistent with what is known about pre-whaling presence and movement patterns, or if changes in whale distribution reflected altered oceanic regimes, prey availability, or increased anthropogenic pressures. The evidence suggested that fin whale populations in the northeast Pacific Ocean are repopulating areas along the BC coast recognized as part of their historic range. However, they are recovering in a different ocean than they were removed from, which makes them increasingly vulnerable to new anthropogenic threats. The sightings data suggested that, at least for the west coast of Vancouver Island, this repopulation has occurred over a relatively short period, with fin whales still absent from regular surveys as recent as the early 2000’s. The recent acoustic recordings suggested their presence is not transitory, but that fin whales may be using locales along the BC coast for feeding and breeding activities.